Megaesophagus by persistence of the right aortic arch in a German shepherd dog (Veterinary Science, 2017)
The authors report the occurrence of a megaoesophagus in a German Sheepdog puppy secondary to the persistence of the arterioso ligament. The three-month old patient had a record of regurgitation which became evident after weaning, dyspnoea and delayed growth. A simple x-ray of the thorax was made as a complementary diagnostic test. The patient was subjected to a left intercostals thoracotomy to dissect the arterioso ligament and free the oesophagic constriction. After surgery, a soft diet from an elevated level was indicated. At the end of the post-operatory period, the patient showed improved clinical signs despite the persistence of the megaoesophagus. The combination of surgical procedure and the characteristics and modality of the diet proved to be the right treatment.
Keywords: Dog; Megaesophagus; Ductus arteriousus